Controlling Molecular Weight of a High Efficiency Donor‐Acceptor Conjugated Polymer and Understanding Its Significant Impact on Photovoltaic Properties. (14th March 2014) - Li, Wentao; Yang, Liqiang; Tumbleston, John R.; Yan, Liang; Ade, Harald; You, Wei
<x xml:space="preserve">Abstract</x> The molecular weight (MW) of PBnDT‐FTAZ can be precisely controlled by adjusting the stoichiometric ratio of the two monomers, following the Carothers equation. The study of a set of PBnDT‐FTAZ polymers with different MWs reveals that the MW significantly influences the morphology and structural order of PBnDTFTAZ in its bulk heterojunction solar cells, with the highest efficiency (over 7%) achieved with the use of a MW of 40 000 g mol−1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>